Discrete Ligand Binding and Electron Transfer Properties of ba3-Cytochrome c Oxidase from Thermus thermophilus: Evolutionary Adaption to Low Oxygen and High Temperature Environments - Koutsoupakis, Constantinos; Soulimane, Tewfik; Varotsis, Constantinos (My University, 2019)
Cytochrome c oxidase (CcO) couples the oxidation of cytochrome c to the reduction of molecular oxygen to water and links these electron transfers to proton translocation. The redox-driven CcO conserves part of the released free energy generating a proton motive force that leads to the synthesis of the main biological energy source ATP. Cytochrome ba3 oxidase is a B-type oxidase from the extremely thermophilic eubacterium Thermus thermophilus with high O2 affinity, expressed under elevated temperatures and limited oxygen supply and possessing discrete structural, ligand binding, and electron transfer properties. The origin and the cause of the peculiar, as compared to other CcOs, thermodynamic and kinetic properties remain unknown. Fourier transform infrared (FTIR) and time-resolved step-scan FTIR (TRS2-FTIR) spectroscopies have been employed to investigate the origin of the binding and electron transfer properties of cytochrome ba3 oxidase in both the fully reduced (FR) and mixed valence (MV) forms. Several independent and not easily separated factors leading to increased thermostability and high O2 affinity have been determined. These include (i) the increased hydrophobicity of the active center, (ii) the existence of a ligand input channel, (iii) the high affinity of CuB for exogenous ligands, (iv) the optimized electron transfer (ET) pathways, (v) the effective proton-input channel and water-exit pathway as well the proton-loading/exit sites, (vi) the specifically engineered protein structure, and (vii) the subtle thermodynamic and kinetic regulation. We correlate the unique ligand binding and electron transfer properties of cytochrome ba3 oxidase with the existence of an adaption mechanism which is necessary for efficient function. These results suggest that a cascade of structural factors have been optimized by evolution, through protein architecture, to ensure the conversion of cytochrome ba3 oxidase into a high O2-affinity enzyme that functions effectively in its extreme native environment. The present results show that ba3-cytochrome c oxidase uses a unique structural pattern of energy conversion that has taken into account all the extreme environmental factors that affect the function of the enzyme and is assembled in such a way that its exclusive functions are secured. Based on the available data of CcOs, we propose possible factors including the rigidity and nonpolar hydrophobic interactions that contribute to the behavior observed in cytochrome ba3 oxidase.
Keywords: Cytochrome c oxidase; Unique ligand binding; Electron transfer; Cytochrome ba3 oxidase